Analisis Hambatan Perkembangan Karakter Disiplin Peserta Didik di Sekolah Dasar - Ervita Rahmawati; Salsa Rahma; Sendi Giwangsa (Universitas Muhammadiyah Kuningan, 2024)
elementary schools. Character development, especially discipline, is the main focus in Indonesian education today. Disciplinary character development is directed at efforts to guide students in understanding, feeling and practicing virtues. The aim of this research is to determine the obstacles that occur in the development of students' disciplinary character in elementary schools. The method used in this research is descriptive qualitative by obtaining data from questionnaires, interviews and previous research documentation. The results showed that the level of discipline of students in general was categorized as very good, especially in the aspect of time and action. The factors that are considered to be obstacles in the development of student discipline include loose enforcement of rules in the school environment, lack of family attention to children, and an unsupportive social environment.